Cu1–xFexO: hopping transport and ferromagnetism. Issue 9 (13th September 2017) - Nasir, Mohd.; Islam, Rakibul; Ahmed, Md. A; Ayaz, Saniya; Kumar, Gautham; Kumar, Sunil; Prajapat, C. L.; Roussel, Frederick; Biring, Sajal; Sen, Somaditya
Abstract : Single phase, sol–gel prepared Cu1 –x Fe x O (0 ≤  x  ≤ 0.125) powders are characterized in terms of structural, electronic and magnetic properties. Using dielectric and magnetic studies we investigate the coupling of electron and spin. The electrical conductivities and activation energies are studied with increasing Fe content. Modelling of experimental conductivity data emphasizes a single hopping mechanism for all samples except x  = 0.125, which have two activation energies. Hole doping is confirmed by confirming a majority Fe 3+ substitution of Cu 2+ in CuO from X-ray photoelectron spectroscopy studies (XPS). Such a substitution results in stabilized ferromagnetism. Fe substitution introduces variation in coercivity as an intrinsic magnetic property in Fe-doped CuO, and not as a secondary impurity phase.